Behemoth - Westerfeld, Scott; Illustrated by Thompson, Keith (New York Simon & Schuster Children Publishing, 2010)
Continues the story of Austrian Prince Alek who, in an alternate 1914 Europe, eludes the Germans by traveling in the Leviathan to Constantinople, where he faces a whole new kind of genetically-engineered warships.
Keywords: Princes -- Genetic engineering -- Animals, Mythical